Ruch sprzeciwu i protestu w systemie totalitarnym: dysydenci w ZSRR - Kirwiel, Eleonora (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The article presents the genesis, structure, and activity of the dissident movement in the USSR in the terminological and axiological context through the prism of public activity, its specificity, and the analysis of ideological diversity.
p. 150-168
Summary in English and Russian.
Keywords: USSR; dissidents; opposition and protest movement; government, resistance to - Soviet Union - history; Soviet Union - intellectual life; dissenters - Soviet Union; Soviet Union - politics and governments - 1945-